2015
DOI: 10.1016/j.ydbio.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Wnt4 is essential to normal mammalian lung development

Abstract: Wnt signaling is essential to many events during organogenesis, including the development of the mammalian lung. The Wnt family member Wnt4 has been shown to be required for the development of kidney, gonads, thymus, mammary and pituitary glands. Here, we show that Wnt4 is critical for proper morphogenesis and growth of the respiratory system. Using in situ hybridization in mouse embryos, we identify a previously uncharacterized site of Wnt4 expression in the anterior trunk mesoderm. This expression domain ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 55 publications
(61 reference statements)
2
43
0
Order By: Relevance
“…The Wnt signaling pathway is important for embryonic development, tissue regeneration and homeostasis (15,16). In the present study, certain Wnt signaling genes were observed to be aberrantly expressed in SCNT embryo, such as the expression of Wnt3A, FZ3, LEF1 and APC.…”
Section: Discussionmentioning
confidence: 50%
“…The Wnt signaling pathway is important for embryonic development, tissue regeneration and homeostasis (15,16). In the present study, certain Wnt signaling genes were observed to be aberrantly expressed in SCNT embryo, such as the expression of Wnt3A, FZ3, LEF1 and APC.…”
Section: Discussionmentioning
confidence: 50%
“…Following Tbx4 expression, Gli1 (a direct S onic H edge h og (Shh) signaling transcriptional target) is detected at E10.5–11.5[9], and it remains activated for the development of bronchial and vascular smooth muscle cells and various stromal cell populations in murine lungs[9, 10]. Following Shh signaling, it is speculated that Wnt singling is required for further differentiation of mesodermal progenitors into pericytes, resident interstitial fibroblasts, and smooth muscle cells[9, 11, 12]. Pericytes appear to arise from Foxn1 -expressing perivascular progenitor cells, which were shown to give rise to several distinct populations of PDGFRß + NG2 + pericytes, some of which co-express PDGFRα and collagen 1[13].…”
Section: Mesodermal Development In the Lungmentioning
confidence: 99%
“…We examined tumors related to tissues that require WNT4 in development (eg. kidney, adrenal, lung, ovary, uterus [45][46][47][48]), and identified tumors that over-expressed WNT4 mRNA (Figure 5A). Comparing WNT4 high versus other tumors, we looked for differences in protein signaling in RPPA data (reverse phase protein array).…”
Section: Atypical Wnt4 Signaling Functions In Diverse Tumor Typesmentioning
confidence: 99%